Dinner in one : exceptional & easy one-pan meals - Clark, Melissa (Clarkson Potter/Publishers, 2022)
"100 all-new super-simple and incredibly delicious one-pot, one-pan, one-sheet--one-everything!--recipes from the New York Times star food writer and bestselling author of Dinner in French. Melissa Clark brings her home cook's expertise and no-fuss approach to the world of one-pot/pan cooking. With nearly all of the recipes being made in under one hour, the streamlined steps ensure you are in and out of the kitchen without dirtying a multitude of pans or spending more time than you need to on dinner. Expect to find a bevy of sheet-pan suppers (Miso-Glazed Salmon with Roasted Sugar Snap Peas), skillet dinners (Cheesy Meatball Parm with Spinach), Instant Pot® pinch hitters (Cheaters Chicken and Dumplings), comforting casseroles (Herby Artichoke and Gruyere Bread Pudding) that you can assemble right in the baking dish, crowd-pleasing one-pot pasta meals (Gingery Coconut Noodles with Shrimp and Greens), vegetable-forward mains, and dozens of tips for turning a vegetarian or meat-based recipe vegan. And since no dinner is complete without dessert, you'll find a chapter of one-bowl cakes, too--from an Easy Chocolate Fudge Torte to a Ricotta-Olive Oil Pound Cake. These are simple, delicious recipes for weekdays, busy evenings, and any time you need to get a delicious, inspiring meal on the table quickly--with as little clean-up as possible"--